Outcome measures in European patients with haemophilia: Survey of implementation in routine clinical practice, perception of relevance and recommendations by European treaters in the EHTSB. Issue 2 (27th October 2016) - Hermans, C.; Klamroth, R.; Richards, M.; de Moerloose, P.; Garrido, R. P.; ,
Abstract : Introduction: This study was conducted to evaluate the current implementation of outcome measures in routine clinical haemophilia practice and to explore and appreciate the perception of the relevance of such measures by treaters. Methods: A survey was completed by 19 of the 26 physicians involved in the European Haemophilia Therapy Strategy Board (EHTSB). Employing an extensive inventory of outcome measures used in patients with haemophilia, information was collected about the frequency of data collection and the subjective appreciation of their importance during clinic review. Results: The survey revealed that most treaters currently collect data that are mainly related to the haemostatic treatment (consumption of concentrates) and the bleeding symptoms (number and location of bleeds) in a non‐uniform and non‐standardized way. By contrast, functional, physical and quality of life scorings are rarely used and show considerable heterogeneity between treaters. Also, many disparities emerged between practice and perception, in particular quality of life data that are perceived as being important but for most of the time are not collected. Conclusions: This survey represents, in our view, the first attempt to evaluate the actual utilization of outcome measures in haemophilia care. While the value of outcome measures is appreciated, they are not assessed regularly. Therefore, there is a need to include appropriate performance indicators (outcome measures) of haemophilia care in routine clinical practice. Consensus recommendations to provide a framework for achieving this aim are provided.